Tidayu ethnic harmonization in semiotic review of face negotiations conflict styles - Rustono Farady Marta; Merry Merry; Febryan Kurniawan; Herda Seftira; Mercedes Amanda (EduLite: Journal of English Education, Literature and Culture, 2021)
The various ethnic groups with distinctive characteristics of each culture in Indonesia have consequences for potential conflicts among them. Tidayu ethnicity is a complete reflection of the interwoven between the three dominant ethnicities in the West Kalimantan region, including: Tionghoa, Dayak, and Malay. This study aims to reveal the meaning of the various signs displayed by the style of inter-ethnic conflict in a video show entitled “Bhinneka Tunggal Ika” with a review of the face negotiation theory proposed by Stella Ting-Toomey. The Thomas Albert Sebeok's Six Sign Semiotics method is used to examine the audio-visual data. The results of the research show that there is a harmonization of signs of various styles of conflict between ethnic groups, so that it becomes a great strength for the Indonesian Nation and State in particular to increase its social solidarity.